Reassessing contemporary macroeconomics on methodological grounds: A Weberian approach - Peter Galbács (Duke University, Center for the History of Political Economy (CHOPE), 2016)
Through this paper I try to join the lively debate around mainstream economics with a view to calling attention to some methodological aspects. It is aimed at outlining an interpretation based on Max Weber's traditional neoclassical methodology that can help us to find the adequate territory of abstract-idealized mainstream models. Special attention is paid to an assessment of the relationship between models and reality. It is argued here that scrutinizing this relationship should reach beyond the oversimplifying approach of empirical tests. Simultaneously, this assessment gives us a refined set of aspects by the application of which to contemporary macroeconomics some methodological breaks can also be highlighted. These breaches would not have been revealed by a linear narrative.
Keywords: B22; B41; E32; 330; assumptions; realism; instrumentalism; abstraction; idealisation; mainstream economics